2018
DOI: 10.1016/j.stemcr.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation versus Differentiation: Redefining Retinoic Acid’s Role

Abstract: Retinoic acid is commonly used in culture to differentiate stem cells into neurons and has established neural differentiation functions in vivo in developing and adult organisms. In this issue of Stem Cell Reports, Mishra et al. (2018) broaden its role in stem cell functions, showing that retinoic acid is necessary for stem and progenitor cell proliferation in the adult brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Due to the limited knowledge in the area of carotenoid metabolites, functioning as ligands of nuclear hormone ligands and further signalling, it should be discussed whether more ligands and more nuclear hormone mediated signalling is purely seen as beneficial or might also be seen as detrimental for human health. RAR-mediated signalling is responsible for a large variety of physiologically mediated pathways, ranging from central physiological pathways such as the induction of differentiation (352,353) , apoptosis (354,355) , cell cycle control (356)(357)(358) , lipid homeostasis (187,359,360) and proliferation (352,361) , which are of high importance for processes of embryonic development (362,363) , reproduction (364,365) , epidermal homeostasis and regeneration (366,367) , immune responses (368,369) and maintenance of bone, brain, nervous and cardiovascular functions (370)(371)(372) . Too low or too high levels of endogenous ATRA (373) , due to a dysfunctional or stressed retinoid homeostasis, while hard to define what the upper and lower threshold levels are, were seen to be risk factors for various previously mentioned physiological functions and are associated with further disease development, where retinoid signalling is dysfunctional.…”
Section: Carotenoids and Cancermentioning
confidence: 99%
“…Due to the limited knowledge in the area of carotenoid metabolites, functioning as ligands of nuclear hormone ligands and further signalling, it should be discussed whether more ligands and more nuclear hormone mediated signalling is purely seen as beneficial or might also be seen as detrimental for human health. RAR-mediated signalling is responsible for a large variety of physiologically mediated pathways, ranging from central physiological pathways such as the induction of differentiation (352,353) , apoptosis (354,355) , cell cycle control (356)(357)(358) , lipid homeostasis (187,359,360) and proliferation (352,361) , which are of high importance for processes of embryonic development (362,363) , reproduction (364,365) , epidermal homeostasis and regeneration (366,367) , immune responses (368,369) and maintenance of bone, brain, nervous and cardiovascular functions (370)(371)(372) . Too low or too high levels of endogenous ATRA (373) , due to a dysfunctional or stressed retinoid homeostasis, while hard to define what the upper and lower threshold levels are, were seen to be risk factors for various previously mentioned physiological functions and are associated with further disease development, where retinoid signalling is dysfunctional.…”
Section: Carotenoids and Cancermentioning
confidence: 99%
“…Transcription is regulated by the binding of RA to its receptor, RA receptor ( RAR ), which forms a complex with the retinoid X receptor ( RXR ) [ 36 ]. The RA is involved in the differentiation of NSCs into neurons, astrocytes, or oligodendrocytes [ 37 ]. RA activates the Hox gene, which is required for hindbrain development and regulates the head–trunk transition [ 38 ].…”
Section: Inhibiting the Smad Pathway In Ipscs For Neural Differentiationmentioning
confidence: 99%
“…Recent studies have shown that RA induces proliferation in early neurogenesis in the developing mouse cerebral cortex and adult hippocampus ( Mosher and Schaffer, 2018 ). Additionally, it was found that in stem-like glioma cells, RA promotes proliferation ( Choschzick et al, 2014 ; Haushalter et al, 2017 ; Mishra et al, 2018 ).…”
Section: Retinoic Acid and Its Signaling Mechanismmentioning
confidence: 99%